Literasi Digital Mendukung Daya Saing dan Transformasi Digital Menuju Era Society 5.0 - Yesi Hendriani Supartoyo (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
The Indonesian government's support for the digital economy in Indonesia's G20 Presidency in 2022 is to develop several priorities in the Digital Economy Working Group, including those covering digital literacy. The G20 agenda is considered to be a momentum for accelerating digital transformation. Based on the Digital Competitiveness Index 2022 data which mapped digital competitiveness in Indonesia, it was stated that now is the momentum towards Indonesia's digital era. This is one of the pillar indicators of the Digital Society, which will be achieved if the community can improve their digital literacy skills to help support their economy. One of them is through the Digital Literacy Index which is a variable from Human Resources. Society 5.0 is an era where all technology is part of humans themselves. Society 5.0 is a “solution” of the Industrial Revolution 4.0. Society 5.0 is expected to create new value through the development of advanced technology that can reduce the relationship between humans and economic problems in the future. To take advantage of these opportunities and answer these challenges, the Indonesian people are required to have data literacy and technology skills towards Society 5.0. The government through the National Digital Literacy Movement has provided digital knowledge training so that the public can gain access to digital literacy with a target of 12.5 million people per year until 2024. This is in line with the Strategic Priority Project/Major Project of the Government's Work Plan for 2022 in the context of recovery economic and structural reforms, namely aspects of increasing public literacy, especially people's digital literacy.